Anther Culture Ability from Crossess Between Upland and New Plant Types of Rice - Heni Saﬁtri; Bambang Sapta Purwoko; Desta Wirnas; Iswari S. Dewi; Buang Abdullah (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2010)
Anther culture provides rapid route in obtaining pure lines in a single generation through producing green haploid plants that may be spontaneously doubled. This technique has been used for crop improvement especially in rice. The objective of this research was to determine regeneration ability of eight F1s derived from crossess between upland and new plant types of rice and from their four parents through anther culture. Completely randomized design with 25 replications was used in this research. Treatments consisted of four parent lines/varieties i.e. P1 (Fatmawati and BP360E-MR-79-2), P2 (Fulan Telo Gawa and Fulan Telo Mihat) and eight F1s obtained from reciprocal crosses of P1 and P2. Callus induction medium was based on N6 medium + 2.0 mg L-1 NAA + 0.5 mg L-1  kinetin + 10-3  M Putrescine, while regeneration medium was based on MS + 0.5 mg L-1  NAA + 2.0 mg L-1  kinetin + 10-3  M Putrescine. The result indicated that F1 derived from Fatmawati x Fulan Telo Gawa (5.00% green plants per total anther) and their reciprocal (3.80% green plants per total anther) crosses were the most responsive genotypes in rice anther culture (had high anther culture ability). The F1 genotypes were more effective to produce green and doubled haploid plants in rice anther culture than their parents. From this research, 161 double haploid plants (29.81%) from total acclimated green plantlets were obtained.  Keywords: anther culture, upland rice, new plant type of rice